2017
DOI: 10.1007/s00223-017-0245-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of Plasma SDF-1 with Bone Mineral Density, Body Composition, and Hip Fractures in Older Adults: The Cardiovascular Health Study

Abstract: Aging is associated with an increase in circulating inflammatory factors. One, the cytokine stromal cell-derived factor 1 (SDF-1 or CXCL12), is critical to stem cell mobilization, migration, and homing as well as to bone marrow stem cell (BMSC), osteoblast, and osteoclast function. SDF-1 has pleiotropic roles in bone formation and BMSC differentiation into osteoblasts/osteocytes, and in osteoprogenitor cell survival. The objective of this study was to examine the association of plasma SDF-1 in participants in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 38 publications
(61 reference statements)
2
16
1
Order By: Relevance
“…Our results are in line with numerous evidences of multidirectional (patho)physiological links between the skeleton as a dynamic, metabolically active organ and the cardiovascular, renal, liver, endocrine, nervous and immune systems. Our observations complement the results from many previous studies showing positive bi- and multi-directional relationships between osteoporosis, falls and fractures, on one hand, and chronic conditions such as CKD 71 , 85 - 90 , CVDs 91 - 104 , anaemia 105 - 111 , hypoalbuminaemia 112 - 114 and hyperthyroidism 115 - 119 on the other, supporting the concept that osteoporosis is a systemic disease.…”
Section: Discussionsupporting
confidence: 89%
“…Our results are in line with numerous evidences of multidirectional (patho)physiological links between the skeleton as a dynamic, metabolically active organ and the cardiovascular, renal, liver, endocrine, nervous and immune systems. Our observations complement the results from many previous studies showing positive bi- and multi-directional relationships between osteoporosis, falls and fractures, on one hand, and chronic conditions such as CKD 71 , 85 - 90 , CVDs 91 - 104 , anaemia 105 - 111 , hypoalbuminaemia 112 - 114 and hyperthyroidism 115 - 119 on the other, supporting the concept that osteoporosis is a systemic disease.…”
Section: Discussionsupporting
confidence: 89%
“…Unlike the tightly regulated expression/activity of the transmembrane parent form (CD26) on cells and within tissues, the soluble DPP4 (sCD26) is widely present in plasma and other tissue compartments and is constitutively fully enzymatically active (Klemann, et al, 2016;Mortier, et al, 2016). Indeed endogenous levels of soluble DPP4 may not represent a rate-limiting factor, allowing cleavage of most of its substrate pools in those compartments (Carbone, et al, 2017a;Carbone, et al, 2017b).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Common sources are tissue stromal/support cells such as mesenchymal derived cells involved in stem cell niche organization, cardiomyocytes, neural stem cells (NSCs), osteogenic cells, and endothelial cells (Carbone, et al, 2017b;Herberg, et al, 2013b;Mortensen & Hill, 2015). For example, we and others have shown that in the brain astrocytes are the primary constitutive source of CXCL12.…”
Section: Cxcl12 Stromal Cell-derived Factor 1 (Sdf-1)mentioning
confidence: 99%
“…BMSCs are the main source of precursor cells that undergo osteogenic differentiation during fracture healing. The effect of hypoxia on BMSCs homing, proliferation, and differentiation has been widely studied (Carbone et al, ; Wang et al, ). Hypoxia regulates osteogenic cells proliferation and angiogenesis through extracellular regulated protein kinases (ERK)‐1/2 and protein kinase B (AKT) pathway (Nicolaidou et al, ; Guo et al, ).…”
Section: Introductionmentioning
confidence: 99%